2023
DOI: 10.1186/s40359-023-01143-0
|View full text |Cite
|
Sign up to set email alerts
|

How photo editing in social media shapes self-perceived attractiveness and self-esteem via self-objectification and physical appearance comparisons

Abstract: Background As photo editing behavior to enhance one?s appearance in photos becomes more and more prevalent on social network sites (SNSs), potential risks are increasingly discussed as well. The purpose of this study is to examine the relationship between photo editing behavior, self-objectification, physical appearance comparisons, self-perceived attractiveness, and self-esteem. Methods 403 participants completed self-report questionnaires measuri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As a consequence, the elicitation of upward comparisons are likely to facilitate negative feelings [15,40,41]. Specifically, initial evidence has been found that social comparisons generated on Instagram have negative repercussions on well-being [17,18,42]. In agreement with these results, further studies, which were conducted recently, revealed a negative association between social comparisons on SNSs and subjective well-being [43,44].…”
Section: Subjective Well-being Social Comparisons and Snssmentioning
confidence: 68%
See 1 more Smart Citation
“…As a consequence, the elicitation of upward comparisons are likely to facilitate negative feelings [15,40,41]. Specifically, initial evidence has been found that social comparisons generated on Instagram have negative repercussions on well-being [17,18,42]. In agreement with these results, further studies, which were conducted recently, revealed a negative association between social comparisons on SNSs and subjective well-being [43,44].…”
Section: Subjective Well-being Social Comparisons and Snssmentioning
confidence: 68%
“…SNSs provide platforms on which social comparisons are enabled, as self-referential information is continuously presented and retrievable (cf., [8,15]). Instagram, as an image-based medium, provides quick and easy ways to access millions of profiles and use them to collect social comparison information, and allows people to present themselves [16][17][18]. Accordingly, Instagram can meet the basic needs for the social comparison described above.…”
Section: Social Comparisonsmentioning
confidence: 99%
“…In that study, a greater dependency was found among women, with a direct relationship to poor management of social media [90][91][92][93]. In contrast, based on the fieldwork conducted, it was not possible to identify significant differences between the results for men and women [94][95][96][97][98][99].…”
Section: Discussionmentioning
confidence: 99%
“…3). [14] Věda a perspektivy № 2( 33 Now let us take a closer look at each of the stages. Image acquisition -this process involves "capturing" an image using a sensor, such as a camera, and converting it into a format suitable for further use (e.g., a digital image file).…”
Section: Fig2 Examples Of Recognizing Patterns and Objects In Photos ...mentioning
confidence: 99%